MCTS Microsoft Exchange Server 2007 : - Schmied, Will (Wiley, 2007)
This comprehensive book prepares you for Microsoft's new certification, MCTS: Microsoft Exchange Server 2007. Exam 70-236 serves as both the single exam requirement for achieving the MCTS designation as well as the entry exam for the MCITP certification for Exchange Server 2007. Inside, you'll find the practical and in-depth instruction you need, including full coverage of all exam objectives, practical hands-on exercises, real-world scenarios, challenging review questions, and more. The book includes a CD with advanced testing software and electronic flashcards.